PENGARUH CITRA MEREK (BRAND IMAGE) DAN KEPERCAYAAN MEREK (BRAND TRUST) TERHADAP LOYALITAS MEREK (BRAND LOYALTY) (Studi Kasus Pada Konsumen Pasta Gigi Pepsodent di Kota Pontianak) - B11110139, FITRIADI (Jurnal Manajemen Update, 2014)
Business development in the current globalisation period marked with the brand strategy brand image and brand trust aiming to retain customers and create a feeling of satisfaction that will build long-term relationships. Pepsodent toothpaste is a toothpaste brand that has been known by the public. With the various brands of toothpaste, then the impact to competition for get customers. In making a product build brand image and brand trust is the main thing, that must be by the company to increase consumer loyalty. if the brand image and brand trust develoved properly it will give a good overview on the product. This study aims to analyze the influence of brand image and brand trust Pepsodent toothpaste products in Pontianak. This study, used the method of quantitative causal form. In this study, conducted distributing questionnaires to 100 Pepsodent toothpaste products users in Pontianak city, using purposive sampling technique. After that, an analysis of data obtained by using quantitative data analysis. Quantitative analysis includes: Validity and Reliability Tast, Assumptions Classic Test, Multiple Regression Analysis, hypothesis testing via t-test and F-test, and analysis of the determination coefficient (R2). Results of study, it shows that the brand image and brand trust individually and together, significantly influence brand loyalty on Pepsodent toothpaste products in Pontianak. From the test results of partial. it can be seen that brand trust is the more dominant influence onÂ  brand loyalty in Pepsodent toothpaste products in Pontianak city. Keywords: brand loyalty, brand image, brand trust.